REPRESENTASI SENSUALITAS PEREMPUAN DALAM IKLAN ZILINGO (STUDI SEMIOTIKA DENGAN CHARLES SANDERS PIERCE) - UMMY HANIFAH (Institut Bisnis Muhammadiyah Bekasi, 2022)
Mass media and women are likened to two sides of the coin that can’t be separated. Advertising describes women as weak creatures. The role of women that always describe in ads always describes domestic roles. Women are also exploited by the sensuality that they have in their bodies as a means of attraction in the mass media industry. This research is researching the Zilingo version Classy or Glossy. the representation of women in this ad is represented in the form of a dancing woman, flirting with ex her boyfriend, by being exploited with their bodies. The technique used in ads by using jingles or interesting slogans. The research wants to know how Zilingo represented women’s sensuality by selecting signs like pictures or other signs. The approach used in this research is a semiotic theory from Charles Sanders Pierce known as a theory triangle meaning in analyzing the sign. The object of this research consists of words, and pictures in Zilingo's ad. The result shows sensual women, according to Zilingo, describe having slim stature, black hair, and beautiful face and breaking the traditional style of women. Besides that, the Zilingo ad also has a message as a picture frame and social frame. In a picture frame, women try to attract alluring. And in the social image, women are active against the traditional concept of women. Of course, it is suitable with the main purpose of the ad is to persuade consumers in order to use their product, or service in a form of creative advertising strategy.